Research issues and trends in industrial productivity over 44 years. Issue 5 (3rd March 2016) - Jin, Jong Beom; Leem, Choon Seong; Lee, Choong Hyun
Abstract : The purpose of this study is to determine the major issues and potential megatrends in productivity over the past 44 years. Specifically, this has been done by reviewing the productivity literature and productivity trends in the area of manufacturing. Using this, a foundation for the direction of future productivity research is suggested. In this study, productivity-related trends and technology policy data were analysed to derive an initial productivity-related framework. In addition, a productivity issue framework for the academic fields was created by analysing productivity-related literature. Subsequently, trends in productivity studies as well as megatrends were analysed by placing common core issues in two categories. From an analysis of productivity trends, an initial framework of sixteen productivity issues and a productivity issue framework comprising nine productivity issues from our literature analysis were established. By integrating the two frameworks, major productivity-related issues and six megatrends were identified. Our expectation is that the results of this study will serve as a foundation for the future academic studies as well as document manufacturing companies' strategic methods addressing productivity.